(untitled) (ItalianoLinguadue, 2023)
This transdisciplinary study aims to investigate pragmatic and semantic aspects related to a still underexplored area of human communication; namely that involving paraverbal features of written language. In particular, it examines the construction and diffusion of meaning ascribed to traditional and pseudo-traditional typographic mimicry used in commercial signs present in two semiotic landscapes in central areas of Rome and Athens, the capital cities of Italy and Greece. According to previous studies, as well as prosodic features in speech, typography is essential paraverbal and multimodal quality for written communication that can be seen as a code in its own right. Specifically in store naming, typographic mimicry can convey implicit social, political and cultural meaning. Through a methodological approach set on critical discourse analysis, the present study investigates how typographic features present in store names can convey positive ideas linked to the authenticity of the product or business in which they are used. A qualitative diachronic, sociological and linguistic analysis is conducted of both traditional Roman and pseudo-Greek fonts and the two specific semiotic landscapes of Testaccio and Plaka districts in which target typefaces are used for commercial purposes. Finally, interviews are conducted with owners and authors of the signs examined. The findings show that traditional Latin and pseudo-Greek fonts used in commercial signs can implicitly activate presuppositions related to real or commodified authenticity only if present in suitable contexts where the recipients share the same common ground with the issuers. Presupporre l’autenticità attraverso i tratti tipografici delle insegne commerciali Questo studio transdisciplinare si propone di indagare gli aspetti pragmatici e semantici relativi alle caratteristiche paraverbali del linguaggio scritto. In particolare, esamina la costruzione e la diffusione di significato attribuito all’imitazione tipografica tradizionale e pseudo-tradizionale utilizzata nelle insegne commerciali presenti in due paesaggi semiotici nelle zone centrali di Roma e Atene, le capitali di Italia e Grecia. Secondo studi precedenti, oltre alle caratteristiche prosodiche del parlato, la tipografia è una qualità paraverbale e multimodale essenziale per la comunicazione scritta che può essere vista come un codice a sé stante. In particolare, nella denominazione di attività commerciali, la mimica tipografica può veicolare significati sociali, politici e culturali impliciti. Attraverso un approccio metodologico basato sull’analisi critica del discorso, il presente studio indaga su come le caratteristiche tipografiche presenti nei nomi dei negozi possano veicolare idee positive legate all’autenticità del prodotto o dell’azienda in cui vengono utilizzate. Viene condotta un’analisi qualitativa diacronica, sociologica e linguistica dei caratteri tipografici tradizionali romani e pseudo-greci e dei due specifici paesaggi semiotici dei quartieri di Testaccio e Plaka in cui i caratteri tipografici di riferimento sono utilizzati per scopi commerciali. Sono state inoltre effettuate interviste con i proprietari e gli autori dei segni grafici esaminati. I risultati mostrano che i caratteri tradizionali latini e pseudo-greci utilizzati nelle insegne commerciali possono attivare implicitamente presupposti legati all’autenticità reale o mercificata solo se presenti in contesti adeguati in cui i destinatari condividono lo stesso terreno comune con gli autori.